PENYULUHAN BAHAYA PENYALAHGUNAAN NARKOTIKA DAN PSIKOTROPIKA: SINERGI MAHASISWA HUKUM DAN TOKOH MASYARAKAT PANDEGLANG DALAM MEMBANGUN DESA BERSINAR (BERSIH NARKOBA) - Faturohman, Alfin; Alfin Suci Saputra; Hendric Setiawan; Salwa Mahestu; Reza Alfian Hidayat (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The abuse of narcotics and psychotropic substances is a social problem that negatively affects health, social life, and the future of the younger generation. Therefore, preventive efforts through education and counseling are needed. This Community Service Program (PKM) aims to increase public awareness about the dangers of narcotics and psychotropic abuse and their legal consequences through the synergy between law students and community leaders in supporting the Drug-Free Village (Desa Bersinar) program. The activity was conducted at SMAN 2 Pandeglang, Banten using lectures, discussions, and question-and-answer methods. The results showed an increase in participants’ understanding of drug types, the impacts of drug abuse, and legal sanctions related to narcotics and psychotropics. In addition, the activity increased community awareness in maintaining a safe and drug-free environment. Therefore, this counseling activity is expected to become a preventive effort in supporting the realization of a Drug-Free Village in Pandeglang Regency.